Controlling Production Variances in Complex Business Processes - Griffioen, Paul; Christiaanse, Rob; Hulstijn, Joris (Software Engineering and Formal Methods, 2018)
Products can consist of many sub-assemblies and small disturbances in the process can lead to larger negative effects downstream. Such variances in production are a challenge from a quality control and operational risk management perspective but also it distorts the assurance processes from an auditing perspective. To control production effectively waste needs to be taken into account in normative models, but this is complicated by cumulative effects. We developed an analytical normative model based on the bill of material, that derives the rejection rates from the underlying processes without direct measurement. The model enables improved analysis and prediction. If the rejection rate is not taken into account the function of the bill of material as a reference model deteriorates and therefore output measures become more opaque and harder to verify. As a consequence it is extremely difficult or even impossible to assess efficiency and effectiveness of operations. Secondly it is impossible to judge whether net salable assets represent the correct amount and finally it is impossible to assert whether the operations do comply to company standards and applicable laws.